Genetic Modulation of Plasma Protein S Levels by Two Frequent Dimorphisms in the PROS1 Gene - Leroy-Matheron, C.; Duchemin, J.; Levent, M.; Gouault-Heilmann, M. (Thrombosis and Haemostasis, 1999)
We studied two polymorphisms located close to or within the 3’-untranslated (3’-UT) region of the PROS1 gene [an A to G transition at nt 2148 (Pro 626) and an A to C substitution at nt 2698] in 110 healthy volunteers. The allele frequency of the nt 2148 G variant was 35%, and that of the nt 2698 A variant was 27%. We found a relationship between the two dimorphisms (both separately and together) and the plasma total protein S antigen (tPS) level. The impact of the neutral Pro 626 dimorphism was more significant than that of nt 2698 C/A (p = 0.0003 and p = 0.013, respectively). The lowest tPS values were observed in subjects with the Pro 626;nt 2698 GG;CC genotype, and the highest values in those with the AA;AA genotype. Both polymorphisms acted independently of sex and age. The mechanisms by which the two polymorphisms regulate tPS synthesis were not revealed by the studies of platelet mRNA. This study provides the first evidence of a genetic modulation of tPS levels, which, in addition to age and sex, contributes to the wide normal range of tPS in plasma. Determination of these two polymorphisms could be a valuable additional tool for studying PS.